Amphibians and reptiles in the swamps dominated by the palm Raphia taedigera (Arecaceae) in northeastern Costa Rica. - Bonilla-Murillo, Fabián (2013)
The herpetofauna that inhabits Caribbean Costa Rica has received considerable attention in the last two decades. This assemblage includes a total of 141 species of reptiles and 95 amphibians mostly distributed in tropical wet and moist lowland forests. While most information available came from primary and secondary forest sites, little is known about the amphibians and reptiles that inhabit more open habitats, such as wetlands and swamps. For instances, swaps dominated by the yolillo palm Raphia taedigera extend through much of the northeastern Caribbean coast of Costa Rica and eastern Nicaragua, but information about the herpetological community that uses such environments remains practically unknown. This situation reflects the little research conducted in such inhospitable environments. Here, we report the results of an intensive survey conducted to assess the herpetological community that inhabit R. taedigera palm-swamps. A total of 14 species of amphibians and 17 of reptiles have been recorded from these swamps. Amphibians and reptiles that inhabit yolillo swamps have wide distributions along much of Middle America and are considered common species throughout their range. In general, yolillo swamps are poor environments for herpetofauna: richness of reptiles and amphibians is almost two times higher in the adjacent forest than in the palm dominated swamps. Furthermore, most species observed in this swamps can be considered habitat generalists that are well adapted to the extreme conditions imposed by the changes in hydroperiods, reduce understory cover, low tree diversity and simple forest architecture of these environments. Despite similarities in the herpetofauna, it is clear that not all forest species use yolillo habitat, a characteristic that is discussed in terms of physical stress driven by the prolonged hydroperiod and reduced leaflitter in the ground, as these features drive habitat structure and herpetofaunal complexity. Our list of species using yolillo swamps is not definitive, and is likely to grow as more studies are conducted in this unexplored environment.